Escherichia coli ClbS is a colibactin resistance protein. Issue 5 (1st December 2015) - Bossuet‐Greif, Nadège; Dubois, Damien; Petit, Claude; Tronnet, Sophie; Martin, Patricia; Bonnet, Richard; Oswald, Eric; Nougayrède, Jean‐Philippe
Summary: The genomic pks island codes for the biosynthetic machinery that produces colibactin, a peptide‐polyketide metabolite. Colibactin is a genotoxin that contributes to the virulence of extra‐intestinal pathogenic E scherichia coli and promotes colorectal cancer. In this work, we examined whether the pks ‐encoded clbS gene of unknown function could participate in the self‐protection of E . coli ‐producing colibactin. A clb S mutant was not impaired in the ability to inflict DNA damage in HeLa cells, but the bacteria activated the SOS response and ceased to replicate. This autotoxicity phenotype was markedly enhanced in a clb S   uvr B double mutant inactivated for DNA repair by nucleotide excision but was suppressed in a clb S   clb A double mutant unable to produce colibactin. In addition, ectopic expression of clb S protected infected HeLa cells from colibactin. Thus, ClbS is a resistance protein blocking the genotoxicity of colibactin both in the procaryotic and the eucaryotic cells. Abstract : ClbS is a self‐defense protein that, in concert with the prodrug assembly and efflux strategies, prevents DNA damage in Escherichia coli producing the genotoxin colibactin. Mutagenesis of ClbS results in self‐inflicted DNA damage and growth defect of the bacteria, which is aggravated upon inactivation of the nucleotide excision DNA repair system.